Energy Consumption Analysis of Frozen Sandy Soil and an Improved Double Yield Surface Elastoplastic Model considering the Particle Breakage - Junlin He; Zhanyuan Zhu; Fei Luo; Yuanze Zhang; Zuyin Zou (Advances in Civil Engineering)
The stress-strain relationship of frozen soil is a hot research topic in the field of frozen soil mechanics. In order to study the effect of particle crushing on the stress-strain relationship, a series of triaxial compression tests for frozen sandy soil are performed under confining pressures from 1 to 8 MPa at the temperatures of −3 and −5°C, and the energy consumption caused by particle breakage is analyzed during the triaxial shear process based on the energy principle. It is found that the energy consumption caused by the particle breakage presents a hyperbolic trend with axial strain. In view of the obvious advantages of the double yield surface elastoplastic model in describing soil dilatancy, stress path effect, and stress history influence, a modified double yield surface elastoplastic model for frozen sandy soil is proposed based on the energy principle. The validity of the model is verified by comparing its modeling results with test results. As a result, it is found that the stress-strain curves predicted by this model agree well with the corresponding experimental results under different confining pressures and temperatures.